Antimicrobial activities of pomegranate rind extracts: enhancement by addition of metal salts and vitamin C - Kelly Alison F; Fielder Mark D; Gould Simon WJ; McCarrell Erin M; El Sankary Waffa; Naughton Declan P (BMC, 2008)
Abstract Background Punica granatum L. or pomegranates, have been reported to have antimicrobial activity against a range of Gram positive and negative bacteria. Pomegranate formulations containing ferrous salts have enhanced although short-term, antibacteriophage activities which are rapidly diminished owing to instability of the ferrous combination. The aim of this study was to determine the antimicrobial activities of combinations of pomegranate rind extracts (PRE) with a range of metals salts with the added stabiliser vitamin C. Methods PRE solutions, prepared by blending rind sections with distilled water prior to sterilisation by autoclaving or filtration, were screened with a disc diffusion assay using penicillin G as a control. Suspension assays were used to determine the antimicrobial activities of PRE alone and in combination with salts of the following metals; Fe (II), Cu (II), Mn (II) or Zn (II), and vitamin C, against a panel of microbes following exposure for 30 mins. The test organisms included Staphylococcus aureus, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa and Proteus mirabilis. Results The screening assay demonstrated that PRE exhibited activity against the Gram positive organisms at 24 h with no observable effect on any of the Gram negative bacteria. However, after 12 h, zones of inhibition were only observed for Ps. aeruginosa. In contrast, using the suspension assay, addition of Cu (II) salts to PRE solutions extended the activities resulting in no detectable growth being observed for the PRE/Cu (II) combination against E. coli, Ps. aeruginosa and P. mirabilis. Minimal antimicrobial activity was observed following incubation with Fe (II), Mn (II) or Zn (II) salts alone or in combination with PRE against any of the organisms in the test panel. The addition of vitamin C markedly enhanced the activities of both PRE/Fe (II) and PRE/Cu (II) combinations against S. aureus. Conclusion This is the first report demonstrating the enhanced efficacy of PRE/metal salt combinations in the presence of the stabilising agent vitamin C, to which all isolates were sensitive with the exception of B. subtilis. This study has validated the exploration of PRE along with additives such as metal salts and vitamin C as novel antimicrobial combinations.